Novel insights into PLMN-13PT ceramics: impact of spark plasma sintering on compositional and dielectric properties (2024)
ABSTRACT: This study investigates the effects of Spark Plasma Sintering (SPS) on the physical, structural, microstructural, dielectric, and optical properties of on 87[Pb(1−y)Lax(Mg1/3Nb2/3)O3]-13PbTiO3, (PLMN-13PT) ceramics. The primary objective was to evaluate how SPS influences the densification, grain growth, and compositional variations of these ceramics, which are critical for electronic device applications. The results demonstrate that SPS effectively achieves high relative density while suppressing grain growth, leading to a more homogeneous microstructure. However, the rapid densification process also induces compositional variations that significantly impact the dielectric properties, including the reduction of undesirable phases like pyrochlore, which are detrimental to performance. These findings highlight the potential of SPS for optimizing PLMN-13PT ceramics, enhancing their suitability for the miniaturization of multifunctional electronic devices.